Nutritional composition of rice bran submitted to different stabilization procedures - Simone Aparecida dos Santos Conceição Faria; Priscila Zaczuk Bassinello; Marilene de Vuono Camargo Penteado (Brazilian Journal of Pharmaceutical Sciences, 2012)
In order to inactivate enzymatic deterioration, whole rice bran samples were subjected to two stabilization methods. Changes in nutritional value in terms of, concerning chemical composition, minerals and fatty acid content, were evaluated to supplement existing data and promote the utilization of rice bran in the human diet. The following homemade heat treatments were applied: roasting on a conventional stove or heating in a microwave oven. Based on the results, the different heating methods affected sample composition, since the levels of some nutrients of treated samples showed significant changes (p<0.05) compared to corresponding raw samples. The rice bran treated on a conventional stove produced products with lower moisture (5.14±0.10 g/100 g) and nutrients such as sodium 11.8%; palmitic acid 9.9% and stearic acid 8.1%. The microwave oven procedure resulted in better nutrient preservation, with slightly higher moisture content (6.28±0.10 g/100 g), and appears to be a practical and rapid tool for home heat stabilization of rice bran. A fim de inativar a deterioração enzimática, as amostras de farelo de arroz foram submetidas a dois métodos de estabilização. As mudanças do valor nutricional, no que se refere a composição química, os minerais e o conteúdo de ácidos graxos, foram avaliadas para adicionar mais informações aos dados existentes e promover a utilização de farelo de arroz na dieta humana. Os seguintes tratamentos caseiros por calor foram aplicados: torra em forno convencional ou de aquecimento em forno de micro-ondas. Com base nos resultados, os diferentes métodos de aquecimento afetaram a composição das amostras, já que os níveis de alguns nutrientes mostraram alterações significativas (p <0,05), comparado com as amostras cruas correspondentes. O farelo de arroz tratado em fogão convencional forneceu produtos com menos umidade (5,14 ± 0,10 g/100 g) e nutrientes, tais como: de sódio 11,8%; ácido palmítico 9,9% e ácido esteárico 8,1%. O procedimento de forno de micro-ondas resultou em melhor preservação dos nutrientes, com teor de umidade um pouco maior (6,28 ± 0,10 g/100 g), o que parece ser uma ferramenta prática e rápida no tratamento térmico caseiro para o farelo de arroz.